Factors that Influence the Caring Behavior of Nurses in Nursing Practice at the Hospital. Dr. MM Dunda Limboto - Sabirin B. Syukur; Pipin Yunus; Vidrian Rajib Kasim (PROMOTOR, 2024)
Caring behavior can be shown in interpersonal relationships, namely relationships that occur between nurses and patients, where nurses show caring perception behavior through attention, interventions to maintain patient health, and positive energy given to patients. Nurses' caring behavior has started to be good, but there are still some nurses whose caring behavior is bad The purpose of this study is to analyze the factors that influence nurses' caring behavior in nursing practice at the hospital. Dr. MM Dunda Limboto. The design of this study is an Analytical Observational study with a cross-sectional approach. This research was carried out at RSUD. Dr.MM Dunda Limboto. The number of samples was 39 people. The results of the chi-square analysis test research obtained a p-value of  < α 0.00, so it can be concluded that there is a relationship between knowledge to nursing caring behavior, and there is a workload relationship to nurse caring behavior There is, there is an environmental relationship to nurse caring behavior. The existence of this research is expected to increase and increase nurses' awareness of caring behavior so that health services can be carried out effectively. It is recommended that this study be a reference for improving caring services for nurses and other health workers